2013
DOI: 10.1115/1.4023437
|View full text |Cite
|
Sign up to set email alerts
|

Biochemomechanics of Intraluminal Thrombus in Abdominal Aortic Aneurysms

Abstract: Most computational models of abdominal aortic aneurysms address either the hemodynamics within the lesion or the mechanics of the wall. More recently, however, some models have appropriately begun to account for the evolving mechanics of the wall in response to the changing hemodynamic loads. Collectively, this large body of work has provided tremendous insight into this life-threatening condition and has provided important guidance for current research. Nevertheless, there has yet to be a comprehensive model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 132 publications
(256 reference statements)
6
93
0
Order By: Relevance
“…It is possible that in our study, we did not have sufficient statistical power to detect a difference in PWV or aneurysm diameter between the stable AAA and unstable AAA groups. In previous EXPERIMENTAL STUDIES: Assessing the Stability of Aortic Aneurysms with Pulse Wave Imaging Nandlall and Konofagou studies (19,31), investigators showed that aneurysm formation in the murine angiotensin II model is preceded by the formation of fissures in the wall of the aorta. Incomplete remodeling of the wall after the appearance of a fissure could result in structural weaknesses that remain in the saccular wall, thereby rendering rupture more likely.…”
Section: Experimental Studies: Assessing the Stability Of Aortic Aneumentioning
confidence: 99%
“…It is possible that in our study, we did not have sufficient statistical power to detect a difference in PWV or aneurysm diameter between the stable AAA and unstable AAA groups. In previous EXPERIMENTAL STUDIES: Assessing the Stability of Aortic Aneurysms with Pulse Wave Imaging Nandlall and Konofagou studies (19,31), investigators showed that aneurysm formation in the murine angiotensin II model is preceded by the formation of fissures in the wall of the aorta. Incomplete remodeling of the wall after the appearance of a fissure could result in structural weaknesses that remain in the saccular wall, thereby rendering rupture more likely.…”
Section: Experimental Studies: Assessing the Stability Of Aortic Aneumentioning
confidence: 99%
“…Over 75% of these lesions contain an intraluminal thrombus (ILT), which, in many cases, fills the lesion and yields a lumen of nearly normal size despite the extreme dilatation of the aortic wall. There remains a significant controversy over the precise roles an ILT may play in the enlargement and potential rupture of these aneurysms, but it appears that thrombus is important both biomechanically and biochemically [1][2][3]. There is, therefore, a pressing need to understand better the conditions that lead to the formation of an ILT within these potentially life-threatening lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Complex hemodynamics and flow stagnation are often associated with prothrombotic conditions. For example, intraluminal thrombus in abdominal aortic aneurysm (AAA) [57,54] complicates disease progression, and is thought to be strongly coupled to flow stagnation and recirculation. The chaotic flow field in AAAs [3] leads to complex WSS distributions [4] and interesting near-wall flow structures [1].…”
Section: Introductionmentioning
confidence: 99%